2020
DOI: 10.5114/ada.2019.86181
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exhaled breath condensates from children with asthma on endothelial cells cultured in vitro. Do we really know everything about our breath condensate?

Abstract: Introduction: Asthma-associated remodelling involves subepithelial fibrosis and increased vascularization of the bronchial wall. The latter may be associated with excessive production of several angiogenesis regulators which may be found in exhaled breath condensates (EBCs) collected from children with asthma. Aim: To assess the influence of EBC samples of asthmatic children and healthy controls on in vitro cultures of normal human lung microvascular endothelial cells (HLMVEC) and murine endothelial cell line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Our previous study has shown that exhaled breath condensates from healthy children may induce apoptosis in both human and murine endothelial cells [ 5 ]. Moreover, we have found that this phenomenon was cell type-unspecific [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study has shown that exhaled breath condensates from healthy children may induce apoptosis in both human and murine endothelial cells [ 5 ]. Moreover, we have found that this phenomenon was cell type-unspecific [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its activation by a specific ligand (FasL) results in induction of apoptosis through specific adapter molecule-mediated recruitment and activation of a cascade of caspases [ 23 ]. However, it seems unlikely that CD95/Fas receptor would play a key role in our experimental system, since the previous screening of EBC samples did not confirm any significant amounts of FasL, necessary for its activation [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation